(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: Physical training and physical fitness are required to accomplish military missions. Injuries have a great impact on the health and readiness of the military personnel than any other category of medical complaint. Objective: To find out the common types of injuries, causes of injury and place of occurrence among the Bangladesh Armed Forces personnel during their military activities. Materials and Methods: This cross-sectional descriptive study was carried out during the period of March to June 2012. A total of 101 serving Armed Forces Personnel who had injured during military activities and received indoor treatment from orthopedic, surgery, neurosurgery and officers’ ward of CMH, Dhaka were selected. Data were collected in a semi-structured questionnaire through face to face interview. Results: The mean age of the study populations were 31.69 ± 6.7 years and ranged from 18 to 45 years. Among the cases, 83.2% were Army personnel, 9.9% were Navy and 6.9% were from Air Force. Most of the affected cases (55.5%) belonged to fighting arms, 19.8% from support arms and 5.0% from services arms. Maximum (26.7%) cases suffered from knee injury followed by 23.8% vertebral column related injury and 11.9% lower leg injury. Maximum (40.6%) cases sustained injury in training ground followed by 29.7% in the sports ground and 6.9% in operation area. Conclusion: Injury is one of the major causes of morbidity among the members of Armed Forces. Careful study and analysis on training and operational activities of Armed Forces Personnel definitely will explore new dimension to prevent and combat this preventable health burden. Journal of Armed Forces Medical College Bangladesh Vol.14 (1) 2018: 69-72